Creep model of roadway surrounding rock considering hardening effect and damage effect - Hongmiao Lv (PLoS ONE, 2025)
The influence of confining pressure on creep characteristics was analyzed by carrying out creep tests of rocks under different confining pressures. A new creep model of roadway surrounding rock considering the combined influence of hardening effect and damage effect is established by introducing hardening function and damage variable. Combined with the yield function and plastic potential function, the one-dimensional sandstone creep model is extended to the three-dimensional sandstone creep model. Finally, the correctness of the model is verified by experimental data. The results show that the creep model curve of sandstone considering hardening and damage effects is in good agreement with the test curve. Only under the action of failure load, the model curve deviates from the test curve. But on the whole, the correlation coefficient between the two is above 0.90. This shows that the established model is correct. It also comprehensively reflects the common influence mechanism of hardening effect and damage effect of rock in the whole process of creep deformation. Compared with the Nishihara model, the model curve established in this paper better describes the creep curve with accelerated creep characteristics. At the same time, it also better describes the variation of decay creep and stable creep in creep behavior. When studying the influence of hardening effect and damage effect on rock creep behavior, it is necessary to comprehensively consider the combined effects of various influencing factors.In particular, the creep characteristics of different stages of accelerated creep, decay creep and stable creep are studied. Therefore, the established model can better simulate the characteristic behavior of different stages in the creep process of rock. It well reflects the influence of hardening and damage characteristics on the creep behavior of rock.